Improving lipoplex-mediated gene transfer into C6 glioma cells and primary neurons - Cruz, M. Teresa Girão da (2004)
The development of methodologies for gene transfer into the central nervous system is crucial for gene therapy of neurological disorders. In this study, different cationic liposome formulations were used to transfer DNA into C6 glioma cells and primary hippocampal and cortical neurons by varying the nature of the helper lipid (DOPE, Chol) or a mixture of DOPE and cholesterol (Chol) associated to DOTAP. In addition, the effect of the lipid/DNA (+/-) charge ratio, the association of the ligand transferrin to the lipoplexes, and the stage of differentiation of the primary cells on the levels of transfection activity, transfection efficiency, and duration of gene expression were evaluated. Mechanistic studies were also performed to investigate the route of delivery of the complexes into neurons. Our results indicate that DOTAP:Chol (1:1 mol ratio) was the best formulation to transfer a reporter gene into C6 glioma cells, primary hippocampal neurons, and primary cortical neurons. The use of transferrin-associated lipoplexes resulted in a significant enhancement of transfection activity, as compared to plain lipoplexes, which can be partially attributed to the promotion of their internalization mediated by transferrin. While for hippocampal neurons the levels of luciferase gene expression are very low, for primary cortical neurons the levels of transgene expression are high and relatively stable, although only 4% of the cells has been transfected. The stage of cell differentiation revealed to be critical to the levels of gene expression. Consistent with previous findings on the mechanisms of cell internalization, the experiments with inhibitors of the endocytotic pathway clearly indicate that transferrin-associated lipoplexes are internalized into primary neurons by endocytosis. Promising results were obtained in terms of the levels and duration of gene expression, particularly in cortical neurons when transfected with the Tf-associated lipoplexes, this finding suggesting the usefulness of these lipid-based carriers to deliver genes within the CNS.